HUBUNGAN SPECIFIC GRAVITY KAYUDAUN TERHADAP SERAT DAN KUALITAS PULP (THE RELATIONSHIP OF HARDWOOD SPECIFIC GRAVITY TO FIBER AND PULP QUALITY) - Wawan Kartiwa Haroen (Center for Pulp and Paper, 2017)
The demand for hardwood pulp increased due to the limited hardwood in several countries and its advantage as raw material for paper or paper boards. The hardwood has a specific grafity ranging from low to high that causes the quality of pulp produced not uniform. The observation of specific gravity, fiber morphology, and chemical content of hardwood; and the quality of hardwood pulp have been done. FAO data were used to evaluate the fiber length, fiber wall, lignin, extractives, Kappa Number, and the quality of sulphate pulp. The sulfidity, active alkali, solid to liquor ratio, temperature, and cooking time of pulping process were 25%, 17%, 1 :4, 170°C, and 3.5 hours, respectively. The specific gravity of hardwood in the range of 0.30 to 0.99 was grouped into seven classes and analyzed by statistical regression. The specific gravity of the hardwood was associated withfiber morphology, chemical content, pulping, and pulp quality. The results showed that tha specific gravity of wood affects certain parameters with regression equation model that can be used for the selection ofwood raw materials for sulphate pulping. There is a tendency that the specific gravity can influence the hardwood fiber wall thickness, lignin content, pulp yield, Kappa Number, and the physical properties of pulp for tear and tensile srength. ABSTRAKPermintaan terhadap pulp kayudaun terjadi peningkatan akibat terbatasnya kayudaun di beberapa negara dan keunggulannya sebagai bahan baku kertas atau karton. Kayudaun memiliki specific gravity rendah sampai tinggi, menyebabkan kualitas pulp yang dihasilkan tidak seragam. Pengamatan specific gravity, morfologi serat,dan kandungan kimia kayudaun, serta kualitas pulp telah dilakukan. Evaluasi dilakukan menggunakan data FAO terhadap panjang serat, dinding serat, kadar lignin, ekstraktif, bilangan Kappa, dan kualitas pulp sulfat.Kondisi pemasakan sulfiditas 25%, alkali aktif 17% , ratio 1:4, suhu 170 o C, dan waktu 3,5 jam. Specific gravity kayudaun 0,30-0,99 dikelompokkan kedalam tujuh kelas dan dianalisis dengan statistik regresi. Specific gravity kayu sebagai data tetap dihubungkan dengan morfologi serat, kimia kayu, pulping, dan kualitas pulp. Hasil menunjukkan bahwa specific gravity mempengaruhi parameter tertentu dengan model persamaan regresi yang dapat digunakan untuk seleksi bahan baku hardwood untuk pembuatan pulp sulfat. Terdapat kecenderungan bahwa specific gravity kayudaun dapat mempengaruhi ketebalan dinding serat, kadar lignin, rendemen pulp, bilangan Kappa, sifat fisik pulp untuk sobek, dan tarik.